Perspective Javanese Employee on Pursuing Wealth Finding From an Ethnography Analysis - Medysia Novittaqa S; Oktafianna, Hana; Safira, Seera; Heikal, Jerry (Jurnal Indonesia Sosial Sains, 2026)
Problems economy can happen all over society. Both those who have income tall or those who have income low. The Javanese are Indonesia's most populous ethnic group, and the majority have migrated throughout the archipelago. Nevertheless, Javanese culture continues to permeate their daily activities and is transmitted to subsequent generations. A society's culture typically shapes a person's point of view, conduct, morals, and ethics, which may directly or indirectly influence how groups behave in everyday situations. Economic issues can arise in any community, largely because many people lack the ability to manage their finances responsibly. This study explores how Javanese people perceive financial planning and wealth accumulation. An ethnographic qualitative approach was employed, using in-depth interviews to collect data from Javanese employee respondents. The findings reveal that most respondents focus on wealth planning for future life security, with three main themes emerging: wealth accumulation, wealth preservation, and wealth planning. This study contributes to understanding the intersection between cultural values and financial behavior among Indonesia's largest ethnic group.